2016
DOI: 10.4103/2152-7806.194145
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant depression and anxiety negatively affect pain outcomes in surgically managed young patients with trigeminal neuralgia: Long-term clinical outcome

Abstract: Background:Onset of trigeminal neuralgia (TN) is uncommon in young adults with less favorable benefit from surgical interventions. The aim of this study was to evaluate the role of concomitant psychosomatic disorders in long-term surgical outcomes in this population.Methods:Twenty-one patients younger than 30 years of age were diagnosed initially as having medically refractory TN, and each patient underwent microvascular decompression (MVD) as initial surgical management. Correlation of clinical outcome and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…These findings are consistent with the expression of GABA A Rs along sensory axons ( Bhisitkul et al., 1990 ; Oyelese et al., 1997 ), with the well-documented role of GABA A R signaling in trigeminal pathway nociception ( Dieb and Hafidi, 2015 ; Jang et al., 2017 ; Kaushal et al., 2016 ; Martin et al., 2010 ; Wei et al., 2013 ), with the efficacy of GABA-modulating drugs in some patients with TN ( Granger et al., 1995 ; White et al., 2000 ) ( Table S6 ), and with the established importance of GABA A R disinhibition and consequent neuronal hyperexcitability in neuropathic pain ( Dieb and Hafidi, 2015 ; Jang et al., 2017 ; Martin et al., 2010 ). These observations support our speculation that frequent co-occurrence of anxiety, depression, and other psychiatric conditions with TN, especially those in younger patients ( Mousavi et al., 2016 ) (often unresponsive to MVD) ( Hamlyn, 1997a ), may reflect pleiotropy of germline variants impacting other aspects of GABA signaling.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with the expression of GABA A Rs along sensory axons ( Bhisitkul et al., 1990 ; Oyelese et al., 1997 ), with the well-documented role of GABA A R signaling in trigeminal pathway nociception ( Dieb and Hafidi, 2015 ; Jang et al., 2017 ; Kaushal et al., 2016 ; Martin et al., 2010 ; Wei et al., 2013 ), with the efficacy of GABA-modulating drugs in some patients with TN ( Granger et al., 1995 ; White et al., 2000 ) ( Table S6 ), and with the established importance of GABA A R disinhibition and consequent neuronal hyperexcitability in neuropathic pain ( Dieb and Hafidi, 2015 ; Jang et al., 2017 ; Martin et al., 2010 ). These observations support our speculation that frequent co-occurrence of anxiety, depression, and other psychiatric conditions with TN, especially those in younger patients ( Mousavi et al., 2016 ) (often unresponsive to MVD) ( Hamlyn, 1997a ), may reflect pleiotropy of germline variants impacting other aspects of GABA signaling.…”
Section: Discussionsupporting
confidence: 88%
“…Neuropathic pain affecting the trigeminal system, in particular, is frequently associated with negative affective states, including a high incidence of depression, anxiety, and sleep disorders (Wu et al, 2015, Mousavi et al, 2016, Smith et al, 2013). Patients with trigeminal neuralgia and traumatic trigeminal neuropathic pain also suffer from hypersensitivity to light touch and temperature, often accompanied by a more persistent, dull pain in the region of the face innervated by the damaged nerve (Gregg et al, 1979, Dubner et al, 1987, Love and Coakham, 2001, Elias et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] reported that TN due to venous compression is rare (5.8%), others documented a high rate in TN patients, including young individuals [ Table 3 ]. [ 28 30 31 32 ]…”
Section: Discussionmentioning
confidence: 99%